2022
DOI: 10.25059/2527-2594/retratosdeassentamentos/2022.v25i1.498
|View full text |Cite
|
Sign up to set email alerts
|

Os benefícios e desafios do Programa de Aquisição de Alimentos (PAA) para os agricultores familiares

Abstract: Criado em 2003, o Programa de Aquisição de Alimentos (PAA) tem se mostrado como importante canal de comercialização para os pequenos produtores rurais e relevante política pública de promoção do acesso à alimentação saudável. Ao longo de sua trajetória, diversas alterações normativas e institucionais foram realizadas com o intuito de aprimorar a implementação do programa. Desta forma, este trabalho teve como objetivo analisar os principais benefícios e desafios do PAA para seus beneficiários fornecedores. O mé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
5

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 18 publications
0
5
0
5
Order By: Relevance
“…A participação das mulheres como produtoras teve um incentivo com a inclusão delas nas normativas do Programa de Aquisição de Alimentos (PPA) em 2011, com a Resolução n. o 44, e com o Decreto n. o 7.775/2012, segundo Perin et al (2021). Os autores analisaram a trajetória do PPA, desde sua implementação em 2003 até 2019, e observaram que, até 2008, houve um período de aprendizagem e organização, em um segundo momento, de 2009 até 2013, foram observados resultados significativos com maior protagonismo da Companhia Abastecimento (Conab) e do Ministério de Desenvolvimento Social e Combate à Fome (MDS).…”
Section: Resultados E Discussõesunclassified
“…A participação das mulheres como produtoras teve um incentivo com a inclusão delas nas normativas do Programa de Aquisição de Alimentos (PPA) em 2011, com a Resolução n. o 44, e com o Decreto n. o 7.775/2012, segundo Perin et al (2021). Os autores analisaram a trajetória do PPA, desde sua implementação em 2003 até 2019, e observaram que, até 2008, houve um período de aprendizagem e organização, em um segundo momento, de 2009 até 2013, foram observados resultados significativos com maior protagonismo da Companhia Abastecimento (Conab) e do Ministério de Desenvolvimento Social e Combate à Fome (MDS).…”
Section: Resultados E Discussõesunclassified
“…According to Perin et al (2021), women's participation as producers was boosted by their inclusion in the Food Acquisition Program (PPA) regulations in 2011, with Resolution 44 and Decree 7.775/2012. The authors analyzed the trajectory of the PPA, from its implementation in 2003 until 2019, and observed that until 2008, there was a period of learning and organization, in a second moment, from 2009 until 2013, significant results were observed with greater protagonism of the Supply Company (Conab) and the Ministry of Social Development and Fight against Hunger (MDS).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, both require beneficiaries to be registered in the Single Registry (Cadastro Único). The PAA targets a specific population classified as family farmers, with specific eligibility criteria applying to this category (MDS, 2014;PERIN et al, 2021). Cistern construction, in turn, not only occurs in rural areas but also targets a population concentrated in the Brazilian semi-arid region.…”
Section: Methodsmentioning
confidence: 99%
“…The PAA was established by the Lula administration (2003 -2010) in 2003. With its diverse purchasing modalities, the program is known for creating an institutional market for family farming and small farmers, thereby promoting agricultural production, combating hunger, and connecting production to consumption (GRISA, 2012;PERIN et al, 2021;SAMBUICHI et al, 2019). Lastly, the Cisterns Program was established also during the Lula administration, stemming from a civil society initiative known as the One Million Cisterns Program (P1MC), and it is mainly implemented in partnership with these organizations (ANDRADE and CALMON, 2021;CASTRO, 2021;NOGUEIRA, MILHORANCE, and MENDES, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation